Between sex and power : family in the world, 1900-2000 - Therborn, Göran, 1941- (International library of sociology., 2004)
The institution of the family changed hugely during the course of the twentieth century. In this major new work Göran Therborn provides a global history and sociology of the family as an institution, and of politics within the family.